Main chain thermotropic liquid crystalline polyurethanes containing biphenyl mesogens based on novel AB-type self-polycondensation route: FT-IR and XRD studies - Ranganathan, T.; Gowd, E. B.; Ramesh, C.; Kumar, Anil (Journal of Polymer Science Part A-Polymer Chemistry, 2005)
The detailed mesophasic characterization of main chain liquid crystalline polyurethanes containing biphenyl mesogen, which were synthesized by the novel AB-type self-polycondensation approach, was carried out by using Differential Scanning Calorimetry (DSC), Polarized Optical Microscopy (POM), variable temperature X-ray Diffraction (XRD), and Fourier Transform Infrared (FT-IR) spectroscopic studies. The type of mesophase present in these polymers was identified to be the smectic A phase by POM and XRD studies. The smectic layer thickness was found to increase as the length of the spacer increased. The effect of temperature on the hydrogen bonding was analyzed by FT-IR studies. The curve-fitting analysis of the NH stretching and C=O stretching modes of vibrations indicated a gradual decrease in hydrogen bonding during the transition from the crystalline state to the mesophase. The mesophase to isotropic liquid transition was then accompanied by the complete disappearance of the hydrogen bonding. The biphenyl bands also showed changes during phase transitions due to the coupling of biphenyl vibration modes with the urethane linkage attached to it. (c) 2005 Wiley Periodicals, Inc.
Keywords: FT-IR; liquid-crystalline polymers; polyurethanes; XRD studies

Micellar behavior of dodecyldimethylethyl ammonium bromide and dodecyltrimethyl ammonium chloride in aqueous media in the presence of diclofenac sodium - Mehta, S. K.; Bhasin, K. K.; Kumar, Anil; Dham, S. (Colloids and Surfaces A-Physicochemical and Engineering Aspects, 2006)
The micellar properties of cationic surfactants (S) viz. dodecyldimethylethyl ammonium bromide (DDAB) and dodecyltrimethylammonium chloride (DTAC) in aqueous media in the presence of diclofenac sodium (D) have been investigated by spectroscopic and conductivity measurements. The UV-vis and H-1 NMR studies suggest possible packing of diclofenac sodiurn molecules in the micelles. The conductivity studies were carried out over the temperature range 288.15-308.15 K. The critical micelle concentration (cmc) and degree of counterion binding (beta) of the micelles were determined at different temperatures. Delay in micellisation was observed for both DDAB and DTAC. Thermodynamic parameters (Delta G(m)(0) Delta H-m(0) and Delta S-m(0).) for the micelle system were estimated by applying the charged pseudo-phase separation model. The results of the ternary S/D/W system were analysed in comparison with the reported results of binary SAV system. The Delta G(m)(0) values for the ternary S/D/W system in both the cases show an increase in comparison to the respective binary SAV system. However, Delta S-m(0) decreased with temperature and remained positive in both the systems. At lower temperatures, the micellisation was found to be entropy-driven while at higher temperatures it was enthalpy-dfiven. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: diclofenac sodium; dodecyldimethylethylammonium bromide; dodecyltrimethylammoniurn chloride; Electrical conductivity; spectroscopic measurements

Measurements and molecular interactions for N,N-dimethylformamide with ionic liquid mixed solvents - Attri, Pankaj; Reddy, P. Madhusudan; Venkatesu, P.; Kumar, Anil; Hofman, T. (Journal of Physical Chemistry B, 2010)
To understand the molecular interactions between N,N-dimethylformamide (DMF) with two families of ionic liquids (ILs), we have measured thermophysical properties such as densities (rho) and ultrasonic sound velocities (a) over the whole composition range at 25 degrees C under atmospheric pressure. The excess molar volume (V(E)) and the deviation in isentropic compressibilities (Delta K(s)) were predicted using these properties as a function of the concentration of IL. These results are fitted to the Redlich-Kister polynomials. The materials investigated in the present study included two families of ILs such as ammonium salts and imidazolium salts. Diethylammonium acetate ([Et(2)NH][CH(3)COO], DEAA), triethylammonium actetate ([Et(3)NH][CH(3)COO], TEAA), triethylammonium dihydogen phosphate ([Et(3)NH][H(2)PO(4)], TEAP), and triethylammonium sulfate ([Et(3)NH][HSO(4)], TEAS) are ammonium salts and l-benzy1-3-methylimidazolium chloride (Bmiml[Cl]) belongs to the imidazolium family. The intermolecular interactions and structural effects were analyzed on the basis of the measured and the derived properties. A qualitative analysis of the results is discussed in terms of the ion dipole, ion-pair interactions, and hydrogen bonding between ILs and DMF molecules and their structural factors.